Test data analysis of the thermodynamic vent system-augmented top spray injector liquid nitrogen transfer experiments. (15th September 2022) - Hartwig, Jason; Stephens, Jonathan; Rhys, Noah; Clark, Justin; LeClair, Andre; Majumdar, Alok
Highlights: First ever thermodynamic vent system-augmented cryogenic propellant transfer. TVS-injector permits a non-vented fill through main vent valve. TVS-injector can recover a stalled flow. TVS-injector opens an enhanced condensation heat transfer path between injector metal and ullage. Abstract: Traditionally, a cryogenic tank must be pre-chilled to some "target" temperature before the main vent valve can be closed to attempt a non-vented fill (NVF) of cryogenic liquid propellant. This methodology is particularly attractive for performing in-space transfer of cryogens due to the unknown location of the liquid/vapor interface in microgravity and the high likelihood of venting liquid if the vent valve is opened during transfer. This paper presents in-depth test data analysis of a Thermodynamic Vent System (TVS) augmented injector used for cryogenic tank chilldown and fill experiments of a thin-walled Titanium tank. Eight tests were conducted using liquid nitrogen across a range of inlet conditions and boundary conditions, and three different chilldown/fill methods. For four of the tests, the injector sprays liquid into the tank as normal, but also uses a TVS heat exchanger to cool the metallic injector itself as well as the main incoming liquid stream. Results show that using the TVS augmented injector simplifies transfer operation via enhanced condensation at the injector surface at the cost of sacrificing only a small amount of propellant.